Invasive and Ultrasound Based Monitoring of the Intracranial Pressure in an Experimental Model of Epidural Hematoma Progressing towards Brain Tamponade on Rabbits - Konstantinos Kasapas; Angela Diamantopoulou; Nicolaos Pentilas; Apostolos Papalois; Emmanuel Douzinas; Gregorios Kouraklis; Michel Slama; Abdullah Sulieman Terkawi; Michael Blaivas; Ashot Ernest Sargsyan; Dimitrios Karakitsos (The Scientific World Journal)
Introduction. An experimental epidural hematoma model was used to study the relation of ultrasound indices, namely, transcranial color-coded-Doppler (TCCD) derived pulsatility index (PI), optic nerve sheath diameter (ONSD), and pupil constriction velocity (V) which was derived from a consensual sonographic pupillary light reflex (PLR) test with invasive intracranial pressure (ICP) measurements. Material and Methods. Twenty rabbits participated in the study. An intraparenchymal ICP catheter and a 5F Swan-Ganz catheter (SG) for the hematoma reproduction were used. We successively introduced 0.1 mL increments of autologous blood into the SG until the Cushing reaction occurred. Synchronous ICP and ultrasound measurements were performed accordingly. Results. A constant increase of PI and ONSD and a decrease of V values were observed with increased ICP values. The relationship between the ultrasound variables and ICP was exponential; thus curved prediction equations of ICP were used. PI, ONSD, and V were significantly correlated with ICP (r2=0.84±0.076, r2=0.62±0.119, and r2=0.78±0.09, resp. (all P<0.001)). Conclusion. Although statistically significant prediction models of ICP were derived from ultrasound indices, the exponential relationship between the parameters underpins that results should be interpreted with caution and in the current experimental context.